2022
DOI: 10.36941/jesr-2022-0134
|View full text |Cite
|
Sign up to set email alerts
|

Optimism Predictive Ability and Psychological Flexibility among Students during COVID-19 Pandemic

Abstract: This study investigated the optimism predictability and its relationship with psychological flexibility in a convenience sample of 487 Jordanian basic stage students who have faced a lot of psychological and sociological challenges during the outbreak of COVID-19 which has affected the formation of students’ personality, social relationships, psychological and sociological psychology, academic achievement and more importantly their optimism and psychological flexibility. A descriptive analytical approach was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…This notion is echoed in our study, where psychological flexibility emerged as a significant predictor of empathy, underscoring the importance of adaptability in fostering empathic responses (Tullett & Plaks, 2016). Alhamad et al (2022) also highlight a positive relationship between empathy, self-esteem, and psychological flexibility, reinforcing the idea that psychological flexibility is beneficial for emotional and social well-being (Alhamad et al, 2022).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This notion is echoed in our study, where psychological flexibility emerged as a significant predictor of empathy, underscoring the importance of adaptability in fostering empathic responses (Tullett & Plaks, 2016). Alhamad et al (2022) also highlight a positive relationship between empathy, self-esteem, and psychological flexibility, reinforcing the idea that psychological flexibility is beneficial for emotional and social well-being (Alhamad et al, 2022).…”
Section: Discussionsupporting
confidence: 79%
“…For example, dispositional empathy can be forecasted by beliefs related to happiness, such as flexibility and controllability (Tullett & Plaks, 2016). Furthermore, a positive relationship exists between empathy, self-esteem, and psychological flexibility (Alhamad et al, 2022). Psychological flexibility has been linked to reduced impulsivity in smokers and decreased risk aversion (Marcowski et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…M. Ali [63] studied the psychological problems caused by COVID-19 and their relationship to learning stress among Sultan Qaboos University students, revealing moderate psychological problems among the sample. B. Salah [64] found a correlation between psychological resilience and stress resulting from COVID-19 among University students. Previous studies have shown that mindfulness promotes awareness, improves attention, memory, and cognitive processes, reduces distraction and stress, and enhances learning readiness, academic achievement, attention, concentration, self-reflection practises, and psychological well-being in education [65,66].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Consequently, terrorism research, causes and eradication have tackled this issue. In addition, many countries have started building military alliances, enact legislation plans and strategies to counteract terrorism (Rababah et al, 2021;Salah et al, 2022). However, the effort in this context has not been satisfactory because the provided solutions were scratching the surface of the problem not digging its roots and the main reasons for terrorism evolvement.…”
Section: Jordan's Combat Of Terrorismmentioning
confidence: 99%